Design of quad element MIMO array with EBG structure for mutual coupling reduction - Sakib, Md. Abu Tayab; Islam, Md. Rafiqul; Islam, Md. Shazzadul; Asadullah, G. M.; Bashri, Mohd Saiful Riza (IEEE, 2023)
Multiple Input Multiple Output (MIMO) array antennas that may transmit radio waves in various patterns and polarizations have been increasingly important in current telecommunication systems. However, the mutual coupling effect is the major drawback of the MIMO system. Electromagnetic Band Gap (EBG) is a good solution for planar arrays to reduce the effects of mutual coupling. A simple EBG structure has been proposed in this paper to reduce the mutual coupling effect for a quad element (2×2) MIMO array. First, a single inset-fed microstrip patch antenna has been designed that resonates at 4.2 GHz with minimum return loss as low as -40 dB. A rectangular shape EBG structure with a dimension of 6 × 13 mm has been implemented between the radiating patches. Each EBG unit cell consists of 3 rectangular shape slots with a dimension of 2×3 mm. The simulation result shows that the antenna can radiate around 95% of its power to the receiver and gives a good directive pattern as well. The quad-element MIMO array with the EBG structure has a minimum return loss of less than -50 dB and maximum isolation of more than 20 dB. Therefore, a quad-element MIMO array with the proposed EBG structure can provide better performance in 5G applications.